2020
DOI: 10.1111/1475-6773.13560
|View full text |Cite
|
Sign up to set email alerts
|

Employing computational linguistics techniques to identify limited patient health literacy: Findings from the ECLIPPSE study

Abstract: Objective To develop novel, scalable, and valid literacy profiles for identifying limited health literacy patients by harnessing natural language processing. Data Source With respect to the linguistic content, we analyzed 283 216 secure messages sent by 6941 diabetes patients to physicians within an integrated system's electronic portal. Sociodemographic, clinical, and utilization data were obtained via questionnaire and electronic health records. Study Design Retrospective study used natural language processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 80 publications
(187 reference statements)
0
23
0
Order By: Relevance
“…This study is part of the NLM-funded ECLIPPSE Project (Employing Computational Linguistics to Improve Patient-Physician email Exchange), and a detailed review of methods used to develop the Literacy Profile and results and implications of this work can be found in prior reports. [14][15][18][19] Briefly, our sampling frame included over one million secure messages (SMs) exchanged between diabetes patients and providers between 2006 and 2015 at Kaiser Permanente Northern California (KPNC), a fully integrated health system that provides care to ~4.4 million patients and supports a well-developed and mature patient portal (kp .org). We selected diabetes patients for our study because more than 30 million U.S adults are living with diabetes, 20 and one quarter to one third of them has limited HL skills.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of the NLM-funded ECLIPPSE Project (Employing Computational Linguistics to Improve Patient-Physician email Exchange), and a detailed review of methods used to develop the Literacy Profile and results and implications of this work can be found in prior reports. [14][15][18][19] Briefly, our sampling frame included over one million secure messages (SMs) exchanged between diabetes patients and providers between 2006 and 2015 at Kaiser Permanente Northern California (KPNC), a fully integrated health system that provides care to ~4.4 million patients and supports a well-developed and mature patient portal (kp .org). We selected diabetes patients for our study because more than 30 million U.S adults are living with diabetes, 20 and one quarter to one third of them has limited HL skills.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we have shown that the Literacy Profile has high criterion validity with respect to a reference standard of health literacy, as well as significant predictive validity with respect to health outcomes. [18][19] Our current objective is to determine whether the Literacy Profile has sufficient validity across races/ ethnicities to justify applying and scaling it in practice at a scale that could improve clinical care and population health among diverse populations.…”
mentioning
confidence: 99%
“…(2.1%) [89][90][91][92][93]. Other significant SBDH factors include geographic location [24,31,44,70], health literacy [43,47,88,94], social patterns (sexual health, adverse experiences and behavioral attitudes) [33,52,73,95], social environment [41,56,77], health access [21,54,88], living condition [20,31,35], social behavior [54,63,82], and financial insecurity [81,86].…”
Section: Sbdh Typementioning
confidence: 99%
“…Studying and understanding the health literacy from a systemic perspective is based on an understanding of the inputs, processes, relationships, and outputs of many relevant components considered one of the recent research and application directions for developing solutions that limit the effects of this phenomenon [14,15]. The influential relationship between the individual's competencies, system's demands, and its complexities, where health literacy decisions and actions are taken, and the primary health literacy of an individual (health literacy abilities) in this system, is one of the fundamental justifications for this research and its applied directions [10,16]. The health literacy concept is used as a tool to [10]: simplify and understand the health systems, which are often complicated,, improve the service provided; structure services in ways that maximize simplicity of systems and reduce challenges that limit access for services, ensure meeting the necessary health literacy requirements and preferences of all individuals that the healthcare organization serves; and improve patient outcomes and healthcare quality.…”
Section: Introductionmentioning
confidence: 99%
“…MAPPING BETWEEN THE ANALYTIC HIERARCHY PROCESS SCORE AND EVALUATION GAPS www.ijacsa.thesai.org TABLE XIV. MAPPING BETWEEN THE ANALYTIC HIERARCHY PROCESS SCORE AND FIVE POINT EVALUATION GAPS[16] …”
mentioning
confidence: 99%